Parental stress in mothers of children and adolescents with cerebral palsy - Maysa Ferreira Martins Ribeiro; Ana Luiza Lima Sousa; Luc Vandenberghe; Celmo Celeno Porto (Universidade de São Paulo, 2014)
OBJECTIVES: to evaluate parental stress of mothers of children and adolescents with cerebral palsy; to verify whether parental stress undergoes variations according to the level of motor compromise, the child's phase of life, and sociodemographic variables.METHOD: a cross-sectional, descriptive study, with 223 mothers of children and adolescents with cerebral palsy.RESULTS: 45.3% of the mothers presented high levels of stress; there were differences in stress between mothers of children with mild and severe motor impairment; mothers of older children were more stressed than mothers of younger children and of adolescents; paid work and leisure activities reduced the stress.CONCLUSION: mothers of children and adolescents with cerebral palsy, whose children present mild to severe motor impairment are vulnerable to parental stress. Paid work and leisure activities were the factors that contributed most to reducing the stress.